FORMULASI ORALLY DISINTERGRATING TABLET (ODT) EKSTRAK ETANOL DAUN KEMANGI (Ocimum americanum L.) DENGAN VARIASI KONSENTRASI EXPLOTAB® - Yulistia Budianti Soemarie; Hayatus Sa'adah; Tri Marginingsih (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2018)
Bad breath is usually caused by bacteria and leftovers in the mouth. Utilization of natural ingredients that can be used to overcome the problem of bad breath one of them by using basil leaves (Ocimum americanum L.), which has activity as an antibacterial. The development of the preparations was done on basil leaves to overcome bad breath is by formulating the basil leaves ethanol extract into the Orally Disintegrating Tablet (ODT) preparation. The purpose of this study was to investigate the effect of explotab® concentration variations on the physical properties of ODT and to determine the best of concentrations of Explotab® that fulfill the physical properties of ODT. The type of research conducted was an experimental study. Research object was basil leaves ethanol extract formulated into ODT with Explotab® 2% w/b, 4% w/w, 6% w/b and 8% w/w variation. Physical evaluations test then conducted including : the uniformity of weight evaluation, the hardness test, the friability test, and the dissolved time. The results showed that the explotab® concentration variations had an effect on the physical properties of tablets and the formula with the Explotab® 8% b/b concentration was the best formula that could produce the best ODT tablet with physical properties. Keywords : Basil leaves (Ocimum americanum L.), Explotab®, Orally Disintegrating Tablet (ODT)